Amor y bien, los problemas del amor en santo Tomás de Aquino: un estudio desde la perspectiva de María Celestina Donadío Maggi de Gandolfi - Ponce, Manuel Ocampo (Sapientia, 2020)
Without a doubt, love is one of the most important and most difficult themes in the great work of Saint Thomas Aquinas. It is an eminently metaphysical subject, insofar as it has a close relationship with the good, the end, the perfection, the analogy, and the causality. Its relevance lies in the fact that nothing can be more important for the created being than the principle from which it proceeds and the end to which it must arrive thanks to love. That natural or elicit love that the entire universe feels for the end is, in turn, the fundamental principle of the existence of everything created and the goal of all movement that leads towards God as the culmination of all perfection. Love is precisely the key piece found in every process and in every movement. This work is a tribute to Dr. María Celestina Donadío Maggi de Gandolfi for her brilliant career and tireless work in favor of the truth and the promotion of the philosophy of Saint Thomas Aquinas, especially on this theme of love that she develops in her work entitled: Love and good, the problems of love in Saint Thomas Aquinas. It is an attempt to show the brilliance of this splendid work that masterfully exposes the theme of love in the Aquinate.